PENGARUH DISIPILIN SISWA DAN LINGKUNGAN SEKOLAH TERHADAP PRESTASI BELAJAR SISWA MATA PELAJARAN EKONOMI KELAS XI IPS DI SMA NEGERI 1 MOJOLABAN TAHUN AJARAN 2017/2018â€ - -, Novi Triyatmoko -; -, Baedhowi -; -, Salman Alfarisy Totalia - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
Theeaims ofuthis researchaare:i1) toidetermine theiinfluence ofostudent disciplineutoward theelearning achievementoof economicssin classIXI IPS SMAANegerii1iMojolaban,i2) tomdetermine theminfluence ofmschool environmentotoward theolearning achievementoof economicsmin classIXI IPSSSMA Negerii1iMojolaban, anda3) toodetermine thepinfluencemof studentodiscipline andischool environmenttoward theilearningiachievement ofieconomics iniclass XIIIPS SMAANegeri 1oMojolaban. Thisoresearchiis aiquantitativeiresearch.iThe populationiof theiresearch wasiClass XIiIPS  insSMA Negerio1 Mojolabanoin theoacademic yearoofm2017/2018.iThe samplingitechnique usediwas propotionalirandomisampling.iThe numberiof samplesiwasi119irespondents.iTheidataicollectionimethodsiusediwereiinterview questionnaireiandidocumentation. Theidata analysisitechniqueiused wasimultiple lineariregression.               Theeresult ofothe researchhshows thatuthe equityuof theemultiple regressionpisyY = 12,883 + 0,372 X1 + 0,363iX2. Theeregressionicoefficient isopositive whichumeans thatustudent disciplineuis positivelyaand significantlyuinfluential towarduthe learninguachievement ofothesstudents and school environment isupositively andssignificantly influentialotoward theelearning achievementoof theestudents.            Basedoon theeresult ofutheeresearch, itucan be concluded that: (1)sstudent disciplineiis positivelyyand significantlyuinfluentialutoward the learninguachievement ofothe students which isushown byutheeprobability valueoof <0.05o(0.000<0.05), (2) school environment isupositively and significantlyuinfluential towarduthe learning achievement of the students which is shown by the probability value of <0.05 (0.000<0.05), (3) student discipline and school environment simultaneouslyuis positively and significantly influential toward the learning achievement of the students which is shown by the probability value ofo<0.05 (0.019<0.05)eandrR squareevalue of 53.3%. It isoshownothat 53.3% of theelearning achievement ofothe studentsuis influenced by student discipline and school environment, whileethe restuwhichuis 46.7% isuinfluenced byiotherifactorsnot mentioned inithisiresearch.